Pelatihan Senam Bugar Muhamamdiyah bagi Guru dan Siswa Sekolah Muhamamdiyah di Kota/Kab Sukabumi - Nugraheni, Wening; Bachtiar, Bachtiar; Yulianingsih, Ika (Jurnal Surya, 2023)
Senam Bugar Muhamamdiyah Socialization and Training is a training and outreach activity regarding Senam Bugar Muhamamdiyah which can be used as one of the physical activities to improve the degree of physical fitness of students in Muhammadiyah schools and the Muhammadiyah community. This fitness exercise involves all ages and has irreversible movements, so it can be done together. The activity locations were in several Muhammadiyah schools, namely MI Muhammadiyah Cipetir with 287 students and 14 teachers, MTs Muhammadiyah Cipoho 27 students, SMA Muhammadiyah Sukabumi City with 37 students and in Kp. Cigrass Ds. Sela Awi kec. There were 40 people in Sukaraja, Sukabumi Regency, bringing the total activity participants to 405 participants. Activities carried out for 6 months with meetings once a week. Schedule of activities attached. The achievement of the success of the training was 65% of the participants had memorized the Muhamamdoyah fitness movement and the rest had not memorized it well. We can say that the activity went quite well. There were several factors that hindered the implementation of socialization and training including limited time at school which was cut short by the Ramadan holidays and Eid al-Fitr holidays so that it had quite an effect on the results of the Senam Bugar Muhamamdiyah training because participants were cut off for training and when the exercises started again, the participants forgot again with the movements so they had to start over from the beginning in providing training, the characteristics of students who were still difficult to instruct and students' interest in gymnastic activities were still lacking. However, the supporting factors include adequate facilities and infrastructure, teacher participation, and conducive school support.